(3GdMeGjI GdLfGFjI ddYdGbGJ GdYeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3YHOg eMehO HOGjIs; (3TQja SjO cGed s; (3eMehO cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JSYi gPg GdOQGSI Gdi GVaGA GdMeGjI GdLfGFjI Ydi GdYdGbI Hjf GdYeGd h CUMGH GdCYeGd(B: (3ef NdGd JWHjb bGfhf GdYbhHGJ Ydi GdCaYGd GdJi JfJgc GdMbhb GdJi cadgG GdOSJhQ h GdbGfhf(B: (3MJi dG jTGQ HCUHY GdGJgGe Gdi GdbGfhf GdLfGFi GdJbdjOi HGdYLR Yf edGMbI h JLQje GdCaYGd GdJi JfJgc GdJTQjYGJ GdGLJeGYjI(B: (3h JLQje GdGYJOGA Ydi MQjI GdYed(B: (3h GdcTa Yf GdbGSe GdeTJQc Hjf GdLQGFe HhLg YGe h GdLQGFe GdYeGdjI(B: (3h bO WGdYJ gPg GdOQGSI GdMeGjI GdbGfhfjI ddCLQ HGYJHGQ Cf GdCLQ gh ehQO QRb GdYGed GdhMjO(B: (3cPdc WGdYJ gPg GdOQGSI GdMeGjI GdbGfhfjI GdebQQI dMbhb GdYGed GdTNUjI h GdeYfhjI(B: (3h GdMb ai GMJQGe NUhUjGJg ai eLGd YdGbI GdYed(B: (3ceG WGdYJ gPg GdOQGSI cPdc GdCQcGf GdNGUI(B: (3h fYfi HGdCQcGf GdNGUI GdLQGFe GdJi dG JbY GdG ai eLGd YdGbI GdYed(B: (3ceG gh GdMGd ai LQjeI QThI GdeSJNOejf ai GdeTQhY GdNGU YfOeG Jchf LfGjI(B: (3h LQjeI QThI GdeSJNOejf ai GdeTQhY GdNGU YfOeG Jchf LfMI(B: (3h LQjeI JSNjQ GdYeGds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B408-424s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeUGdM GdYeGdjI eMd GdMeGjI GdLfGFjIs; (3MQjI GdYed s; (3efY GdZjQ ef GdYed s; (3bhGYO JTZjd GdeYhbjf GdeDgdjfs; (3bhGYO JTZjd GdCWaGds; (3bhGYO GdYed GdeaQhVI dGYJHGQGJ CNdGbjIs; (3bhGYO GdYed GdeaQhVI dGYJHGQGJ SjGSjIs; (3bhGYO Yed GdCLGfH aj eUQs; (3JLQje eNGdaI bhGYO GdSdGeI hGdUMI GdegfjI hGdCefjI s; (3JLQje eNGdaI GdbhGYO GdeJYdbI HJMOjO SGYGJ GdYed hGdCLGRGJs; (3Mb GdEVQGHs; (3bhGYO GdeSFhdjI GdLfGFjI aj fWGb bGfhf GdYeds; (3GdLQjeI GdYeGdjIs; (3GdLQGFe GdJj JbY ef CUMGH GdYeds; (3GdLQGFe GdJj JbY ef GdYeGds; (3QThe GdYGedjfs; (3JSNjQ GdYeGds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs